2022
DOI: 10.1097/phm.0000000000002051
|View full text |Cite
|
Sign up to set email alerts
|

Peak Age and Performance Trajectories in Para Powerlifters

Abstract: Objective: This study established the age-related performance trajectories in Para powerlifters, thereby presenting valuable information for athlete development. Design: Data on athlete date of birth, body mass, and weight lifted in competition were analyzed for 2079 athletes between 1994 and 2019.Results: Age-related performance trajectories showed that men and women lift their heaviest weights in competition at 36 and 41 yrs of age, respectively. This correspond to the mean age of competitors in the heaviest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…We reported that POD athletes were younger than their NPOD counterparts for men and women. This finding is consistent with previous research reporting that high-performing athletes are younger than their low-performing counterparts (8,12). Similarly, Keogh et al (6) previously reported that stronger athletes are younger than their less strong counterparts (although not statistically significant).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We reported that POD athletes were younger than their NPOD counterparts for men and women. This finding is consistent with previous research reporting that high-performing athletes are younger than their low-performing counterparts (8,12). Similarly, Keogh et al (6) previously reported that stronger athletes are younger than their less strong counterparts (although not statistically significant).…”
Section: Discussionsupporting
confidence: 93%
“…There is a lack of evidence surrounding the sport of PPL, particularly regarding intracompetition strategies. There is some evidence pertaining to nonmodifiable factors, such as the age and sex of elite para powerlifters, which can be used to map the trajectory of their respective careers (12). In addition, research into the anthropometric profiles of elite PPL athletes has been used to demonstrate the relationship between the athlete's upper limb cross-sectional area and their respective 1 repetition maximum (1RM) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence drawn from the studies overviewed in the present review confirms that PP is a safe sports discipline that can be practiced by people with disabilities [ 51 , 52 , 53 , 54 , 55 , 56 ]. However, the data revealed a high rate of chronic overuse injuries of the upper limbs among PP athletes, with the highest injury incidence rate among all other sports, second only to 5-a-side football [ 69 ].…”
Section: Discussionsupporting
confidence: 61%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation